QUE PARADA É ESSA? experiências no Beco da Codorna e nos becos da Rua do Lazer - Silva, Gabriela Neres Batista (2023)
How do experiences affect this subjective relationship with Becos da Codorna and Rua do Lazer, in the city of Goiânia? And what about the people who attend this place? Or with the graffiti present on them? Based on these questions and the walker's methodology, this dissertation was narrated. Therefore, I invite you to walk with me through these alleys, in order to understand the social and visual relationships we have in these places, and also to understand the artistic, political and social occupations that have resulted in their different perspectives. Along this research, I present the relationship of this theme with Visual Culture, as well as key concepts of image, memory and place. Then, I talk about these alleys and their formative process, being that of Codorna, which has this place for loading and unloading merchandise, for parking and, later, museum/cultural equipment, transformed based on occupations of the Hip Hop community, while those on Rua do Lazer, revitalized after so many years, have a relationship with the local community, going through other processes. Finally, I expose these experiences lived in a post-pandemic world by different people, collectives, businesses that demonstrate these visual and political social perspectives.